POLA KOMUNIKASI WARGA BINAAN DAN PEMBIMBING ROHANI RELAWAN DA’WAH MUSLIMAT CENTER DDII DALAM PROGRAM ASIMILASI DI LAPAS WANITA KELAS IIA TANGERANG - Dicky Andika; Saeful Rokhman; Sya'roni Tohir; Santa Lorita (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2020)
The purpose of this study was to determine the communication patterns of female assisted residents in Tangerang Class IIA Lapas after participating in routine studies through an assimilation program with an Islamic approach by the Da'wah Muslimat Volunteer Team of the Dewan Da'wah Islamiyah Indonesia. This qualitative research approach uses a case study method that seeks to describe in detail and comprehensively the patterns of communication between spiritual guides and assisted members of the assimilation program in their interactions while following Islamic enlightenment regularly twice a week. The informants were 7 of the 12 participants of the assimilation program at the Class IIA Lapas Tangerang, Banten. Informants are assisted residents who have undergone half the time of determining the research informants using purposive sampling technique. Collecting data using observation, in-depth interviews with research informants and conducting documentation studies. The results of data collection were analyzed using qualitative data analysis model analysis from Miles and Huberman so that a conclusion was generated.